Participation of peripheral TRPV1, TRPV4, TRPA1 and ASIC in a magnesium sulfate-induced local pain model in rat. (17th December 2016) - Srebro, Dragana; Vučković, Sonja; Prostran, Milica
Highlights: Subcutaneous injection of isotonic solution of magnesium sulfate (MS) produces local pain. MS modulates the activity of TRPV1, TRPV4, TRPA1 and ASICs. ASIC is involved in the pronociceptive effect of pH-unadjusted, but not pH-adjusted MS solution. TRPV1, TRPV4 and TRPA1 antagonists might be used for local treatment of injection-related pain. Abstract: We previously showed that magnesium sulfate (MS) has systemic antinociceptive and local peripheral pronociceptive effects. The role of transient receptor potential (TRP) channels and acid-sensing ion channels (ASICs) in the mechanism of action of MS has not been investigated in detail. The aim of this study was to explore the participation of TRP channels in the pronociceptive action of MS in rats after its intraplantar injection. The paw withdrawal threshold (PWT) to mechanical stimuli was measured by the electronic von Frey test. Drugs that were tested were either co-administered with an isotonic pH-unadjusted or pH-adjusted solution of MS intraplantarily, or to the contralateral paw to exclude systemic effects. We found that the subcutaneous administration of both pH-adjusted (7.4) and pH-unadjusted (about 6.0) isotonic (6.2% w/v in water) solutions of MS induce the pain at the injection site. The pH-unadjusted MS solution-induced mechanical hyperalgesia decreased in a dose-dependent manner as a consequence of co-injection of capsazepine, a selective TRPV1 antagonist (20, 100 and 500 pmol/paw), RN-1734, a selective TRPV4 antagonist (1.55, 3.1 and 6.2 μmol/paw), HC-030031, a selective TRPA1 antagonist (5.6, 28.1 and 140 nmol/paw), and amiloride hydrochloride, a non-selective ASIC inhibitor (0.83, 2.5 and 7.55 μmol/paw). In pH-adjusted MS-induced hyperalgesia, the highest doses of TRPV1, TRPV4 and TRPA1 antagonists displayed effects that were, respectively, either similar, less pronounced or delayed in comparison to the effect induced by administration of the pH-unadjusted MS solution; the ASIC antagonist did not have any effect. These results suggest that the MS-induced local peripheral mechanical hyperalgesia is mediated via modulation of the activity of peripheral TRPV1, TRPV4, TRPA1 and ASICs. Specific local inhibition of TRP channels represents a novel approach to treating local injection-related pain.